Hepatoprotective property of Berberis lycium in paracetamol induced liver injury; An Experimental study - Shah, Furqan Ali; Parveen, Tahira; Shah, Hasnain Ali; Shah, Azhar Ali; Naseem, Riaz; Iqbal, Waheed (ADVANCES IN BASIC MEDICAL SCIENCES, 2021)
Background: The aim of current study is to find out the Hepatoprotective effects of berberis lycium in paracetamol induced hepatic injury in mice. Methodology: This research was carried out in Peshawar Medical College (PMC) Peshawar Pakistan and Kabir Medical College Peshawar. A sample of 30 mice was subdivided in to 6 groups of 5 mice each. Group I was Positive control group and given Silimyrin 50 mg/kg body weight followed by Paracetamol 250 mg/kg/body weight after three hours. Group II was Negative control group and Group III was Normal control group where Paracetamol 250 mg/kg body weight and Normal Saline was given respectively. Group IV, V, VI were given plant extract at respective doses of 100, 200, 400 mg/kg body weight, each followed by Paracetamol 250 mg/kg/body weight after 3 hours. Blood was extracted for determination of ALT, ALP, serum and total protein using standard protocols while tissue samples were isolated for histopathological studies. Results: The test drug produced dose dependent significant decrease in levels of enzymes under study as compared to control while levels of T-protein were significantly increased as compared to control. Furthermore, histopathological studies reveals that the extract of Berberis lycium shows Hepatoprotective effects in dose dependent manners. Conclusion: This study reveals that Berberis lycium shows hepatoprotective properties. Key words: Acetaminophen, Hepatic injury, Berberis Lycium, Hepatoprotective properties